5(z+6)=4(z-8)+z

Simple and best practice solution for 5(z+6)=4(z-8)+z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(z+6)=4(z-8)+z equation:



5(z+6)=4(z-8)+z
We move all terms to the left:
5(z+6)-(4(z-8)+z)=0
We multiply parentheses
5z-(4(z-8)+z)+30=0
We calculate terms in parentheses: -(4(z-8)+z), so:
4(z-8)+z
We add all the numbers together, and all the variables
z+4(z-8)
We multiply parentheses
z+4z-32
We add all the numbers together, and all the variables
5z-32
Back to the equation:
-(5z-32)
We get rid of parentheses
5z-5z+32+30=0
We add all the numbers together, and all the variables
62!=0
There is no solution for this equation

See similar equations:

| 27x+5=23.4x-1 | | 75+20x=35 | | 3x–1=6+2x | | 3m^2-2m+12=0 | | 24x-48÷6=4 | | 5x=11(2x-3)÷2 | | p+3=7-9p | | 12x2+24=0 | | 3x+1=11=2x | | 1/3(9x-12)-6x+15=-19 | | 95x=35x | | 5x=11(2x-3÷2) | | 7(5x-4)=3(8-5x) | | 8m-4=3+8 | | 5x-14+3x+2+x+32=180 | | 8w-8=4w-7 | | 90+5.45x=13.63x | | 4x-6+2x=2(3x-30 | | 5x=11(2x-3/2 | | 2x+6X+3X+8X+4=338 | | -4x+4/3=20 | | x+4X+X-20=180 | | (2y-12)=90 | | (X+2)+(2x+2)=4x+1x+2 | | 27x+5=-x+9.8 | | 20+9x=180 | | x=5=-5x+5 | | 3-2x=3+2x+x+5 | | 65x^2=9 | | 90+5.45x=13.63 | | 16x+.5=16x+.13 | | 27x+5=-24x+5.7 |

Equations solver categories